Site-specific instability in Drosophila melanogaster: The origin of the mutation and cytogenetic evidence for site specificity. - Lim, J.K. (Genetics, 1979)
During a study of delayed mutations, an unstable X chromosome (Uc) was detected. Spontaneous X-linked recessive lethal mutations were detected in 34 of 993 sperm sampled from 50 males carrying this chromosome. All but three of the 34 lethals originated as clusters in three of the 50 males Cytogenetic and complementation analyses revealed 14 intrachromosomal rearrangements: ten inversions, two reverse repeats, one deficiency and one transposition. Eight of the 14 rearrangements have one break in the 6F1-2 doublet and two rearrangements have a break in 6F1-5 of the X chromosome. The remaining four rearrangements have in addition to the aberrations a lethal point mutation between 6F1 and 6F5. Though each of the lethal lines was established from a single lethal-bearing female, chromosome polymorphism is evident in 17 of the 18 lines having rearrangements, with certain aberrations recurring in several lines. The lethal mutations revert frequently to the nonlethal state, and cytological evidence indicates that more than one mutational event may occur at the unstable locus of the chromosome during one generation. Two lethal lines had more than one type of chromosome rearrangement sharing a common breakpoint. These observations are consistent with the view that the instability of the Uc lines is caused by a transposable element capable of site-specific chromosome breaks and perpetual generation of mutations. The mutagenic and genetic properties of transposable elements can be related to the two-mutation theory of KNUDSON (1971) for cancer initiation.